2022
DOI: 10.1111/dth.15553
|View full text |Cite
|
Sign up to set email alerts
|

Fractional CO 2 laser versus microneedling as a transepidermal drug delivery system for the treatment of alopecia areata: A clinical dermoscopic evaluation

Abstract: New treatment modalities are rising for better clinical improvement in alopecia areata. This work aims to evaluate the efficacy of fractional CO2 laser and microneedling as a transepidermal drug delivery in cases with alopecia areata. The study included 30 patients with alopecia areata. All lesions in each patient have received randomly two different treatment modalities, fractional CO2 laser or microneedling followed by triamcinolone acetonide (TA) application according to group assignment. Sessions were done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In agreement with previous studies [ 38 , 43 ], the percentage of improvement of AASI related negatively with high statistical significance to the patient's age and disease duration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous studies [ 38 , 43 ], the percentage of improvement of AASI related negatively with high statistical significance to the patient's age and disease duration.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with us, Soror et al reported significant improvement in grading AA patches treated by FCL plus TA [ 42 ]. Also, Abd El Kawy et al observed ≥ 75% improvement (according to severity of alopecia tool) in 56.7% of AA patches treated by FCL + TA [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference in effectiveness Laser group: no significant adverse effects Pain score significantly less in laser group ( p = 0.002) RCT/1 Omar et al [ 13 ] AA TAC (10 mg/ml) AFL (CO 2 ; Punto, DEKA, Italy) Power: 10 W Dwell time: 500 ms, Stack: 2 Spacing: 700 m 30 participants randomized to monthly laser or microneedling, followed by TAC until resolution or for a maximum of 6 sessions Both groups had a significant reduction in SALT score ( p < 0.001) with reduction in SALT higher in microneedling group than laser group ( p = 0.013) No statistically significant difference in side effects between groups. Only mild pain and erythema were reported RCT/2 Abd ElKawy et al [ 14 ] AA Clobetasol propionate AFL (ER: YAG; XS dynamics Fotona S1-121d, Ljubljana Slovenia) Fluence: 3 J/cm 2 Frequency: 3–5 Hz Mode: short pulse Spot size: 7 mm 30 subjects with AA had lesions randomized to LEADD or topical clobetasol alone. The laser treatment occurred every 2 weeks for 2–3 weeks, followed by one application of topical clobetasol.…”
Section: Resultsmentioning
confidence: 99%
“…A RCT assigned patients to monthly microneedling or AFL (CO 2 ), both followed by application of triamcinolone acetonide (TAC) for six sessions or resolution of lesions. Both groups had a statistically significant reduction in severity of alopecia Tool (SALT) score ( p < 0.001) with a significant difference between groups favoring the microneedling group ( p = 0.013) [ 14 ]. Another comparative study for treatment resistant AA compared microneedling or AFL (CO 2 ), both followed by application of triamcinolone acetonide (TAC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation